Business Strategy Analysis Using Social Based Business Design In Hanisa Fashion Design - Khairotunnissa, Athiyyah (A Social Science and Entrepreneurship Journal, 2024)
Destination from study this is for get design strategy ideal business for applied with use Business Model Canvas on Hanisa Fashion Design. As technique data collection in research, data used sourced from Interview direct and open with source person related that is owner Hanisa Fashion Design. In study this, author use approach descriptive qualitative.